FORMULASI dan PENGUJIAN SALEP EKSTRAK BONGGOL PISANG AMBON (Musa paradisiaca var. sapientum (L.)) TERHADAP LUKA TERBUKA PADA KULIT TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) - Pongsipulung, Grace Riani; Yamlean, Paulina V. Y.; Banne, Yos (UNIVERSITAS SAM RATULANGI, 2012)
Ambon banana weevil contains medicinal properties that are useful in the process ofwound healing. The purpose of this study is to formulate an ointment of Ambon banana(Musa paradisiaca var. sapientum) weevil extract and to test the ointment to heal open woundon the skin of male rat (Rattus norvegicus). This study is experimental descriptive in thelaboratory. Ambon banana weevil extracts used in the manufacture of ointment formulation.The number of tested animals used was 18, with 6 treatment groups, ie injuries withoutointment application, negative control, positive control, banana weevil ointment 10%, bananaweevil ointment 15%, and the banana weevil ointment 20%. All mice were injured with a8wound of 1.5 cm long. The wounds were applied with ointment three times daily. Observationwas conducted everyday from day 0 to day 8. All data was tested statistically using ANOVA(Analysis of Variant) followed bay LSD (Least Significant Difference) test. Qualitative datawere presented descriptively. The results showed that the banana weevil formulation meetsthe ointment test requirement according to Famakope Indonesia Edition III, i.e wounds werenarrowed, scabs were formed, and then wounds were closed. Statistical tests showed thatthere were significant effects on wound healing in white male rats, ie 4.004 > 2.45. Based onthe results of the study it can be concluded that the preparation of an ointment made frombanana weevil met the requirement, and concentration of 10%, 15%, and 20% gave effect tothe healing of open wounds on the skin of white male rats.Keywords: ointment, extract, Ambon banana weevil, wound healing, white male rats.